2017
DOI: 10.1097/ede.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Error Correction for Predicted Spatiotemporal Air Pollution Exposures

Abstract: Background Air pollution cohort studies are frequently analyzed in two stages, first modeling exposure then using predicted exposures to estimate health effects in a second regression model. The difference between predicted and unobserved true exposures introduces a form of measurement error in the second stage health model. Recent methods for spatial data correct for measurement error with a bootstrap and by requiring the study design ensure spatial compatibility, i.e., monitor and subject locations are drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…However, for linear health models with a single pollutant, analytic measurement error corrections have identified relatively small amounts of bias (16,75). Differences in the spatial distribution of monitors and cohort subjects has been shown to introduce bias in some settings (73,76), but its overall impact is unclear (77,78). Finally, our analysis may not be generalizable to non-low-income children, but our focus on this population may be a strength, as there is evidence that low-income children are particularly vulnerable to the effects of pollution (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, for linear health models with a single pollutant, analytic measurement error corrections have identified relatively small amounts of bias (16,75). Differences in the spatial distribution of monitors and cohort subjects has been shown to introduce bias in some settings (73,76), but its overall impact is unclear (77,78). Finally, our analysis may not be generalizable to non-low-income children, but our focus on this population may be a strength, as there is evidence that low-income children are particularly vulnerable to the effects of pollution (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, that approach, like most other measurement error methodology (Alexeeff, Carroll, & Coull, ; Bergen et al, ; Gryparis, Paciorek, Zeka, Schwartz, & Coull, ; Szpiro & Paciorek, ), was developed under a linear health model, and there currently is no analogue for a generalized linear model setting. However, a nonparametric bootstrap procedure can be used to correct the standard errors of trueβ^1 (Bergen & Szpiro, ; Keller et al, ; Szpiro & Paciorek, ).…”
Section: Impact On Health Model Inferencementioning
confidence: 99%
“…Szpiro and Paciorek () suggested that one method for achieving this compatibility is through restricting the cohort to subjects near (in some sense) a monitor. Keller, Chang, Strickland, and Szpiro () adopted this approach in a spatiotemporal setting by restricting to subjects residing within a county with a monitor in an analysis of infant birth weight and particulate matter (PM) exposure using census‐tract level outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Some cohort studies are also affected by spatial incompatibility, which refers to systematic differences in the distributions of locations of monitor sites in a monitoring network relative to locations of members of the population cohort. Spatial incompatibility can result in biased health effect estimates [ 7 , 8 ]. While there is some evidence that land use regression (LUR) models can be transferable to regions not included in the monitoring area [ 9 ], there is little guarantee that this will be the case in other, or even most, settings.…”
Section: Air Monitoring Considerationsmentioning
confidence: 99%